End-of-life parental communication priorities among bereaved fathers due to cancer. Issue 5 (May 2017) - Park, Eliza M.; Deal, Allison M.; Yopp, Justin M.; Edwards, Teresa; Stephenson, Elise M.; Hailey, Claire E.; Nakamura, Zev M.; Rosenstein, Donald L.
Highlights: Web-based survey of bereaved fathers due to cancer. Communication with children about death is a priority for bereaved fathers. Fathers identify maternal wishes about raising children as important to discuss. Communication priorities of fathers do not differ with time since death. Abstract: Objectives: To elicit widowed fathers' perspectives on which domains of parenting-related communication they consider most important for dying parents to discuss at the end of life (EOL). Methods: Two hundred seventy nine fathers widowed by cancer completed a survey about their own depression and bereavement symptoms, their wife's illness, and EOL parental communication priorities. Chi square and Fisher's exact tests and logistic regression were used to evaluate relationships between maternal EOL characteristics and fathers' responses to parenting-related EOL communication priorities. Results: Fathers identified raising children in a manner that reflected maternal wishes, whether/how to talk with children about their mother's death, and how the mother wanted to be remembered as the most important EOL communication domains. Fathers who reported that their dying wives were worried about the children were more likely to prioritize raising children in ways that reflect her wishes (p = 0.01). Other EOL characteristics were not associated with communication domains. Conclusions: Communicating with children and maintaining emotional connection with the deceased parent are important priorities for bereaved fathers who lost a spouse to cancer. Practice implications: Health care providers working with seriously ill parents may improve family outcomes by supporting communication at the EOL between co-parents.